2012
DOI: 10.1103/physrevstper.8.010103
|View full text |Cite
|
Sign up to set email alerts
|

Controlled study on the effectiveness of multimedia learning modules for teaching mechanics

Abstract: We have investigated the impact of using multimedia learning modules (MLM) on the learning of students enrolled in introductory physics courses at California State Polytechnic University, Pomona. One hundred fifty-nine students were randomly registered in two sections of an introductory mechanics course, one of which featured the MLMs. Both sections had the same instructor, participated in class discussions on identical topics, and used the same problem-solving examples. The students in the multimedia group ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
3
24
0
2
Order By: Relevance
“…For example, improved student learning and attitudes towards instruction have been found when reading assignments have been replaced with on-line multimedia videos in physics classes across various institutions [5][6][7]. In particular, it has been shown that students arrive to class better prepared for learning when completing MLMs versus traditional reading assignments for large-enrollment lecture-based courses and hybrid on-line formats [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, improved student learning and attitudes towards instruction have been found when reading assignments have been replaced with on-line multimedia videos in physics classes across various institutions [5][6][7]. In particular, it has been shown that students arrive to class better prepared for learning when completing MLMs versus traditional reading assignments for large-enrollment lecture-based courses and hybrid on-line formats [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A more in-depth discussion of how the authors of the MLMs utilized the relevant literature in the design process is available in reference [8]. Furthermore, the efficacy of the MLMs has been verified in multiple other settings [5][6][7][8][9].…”
Section: Multimedia Learning Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hace una década, se pudo encontrar en la red (entre vídeos, experimentos interactivos en la pantalla, simulaciones y animaciones generadas por el ordenador) al menos 5000 de multimedia que podrían usarse en la enseñanza de la física (Alther et al 2004). Últimamente, se evalúan experimentalmente sus efectos verdaderos en el aprendizaje de la física de los estudiantes (Sadaghiani 2011, Zacharia y Olympiou 2011, Sadaghiani 2012, Jian-hua 2012, Najafipour et al 2013.…”
Section: El Uso De Vídeo En La Enseñanza Y El Aprendizaje De La Físicaunclassified